An Interactive Fuzzy Multi-Objective Optimization Approach for Crop Planning and Water Resources Allocation - Zhou, Huicheng; Peng, Hui; Zhang, Chi (Bio-Inspired Computational Intelligence and Applications, 2007)
A fuzzy multi-objective crop planning model is formulated for determining the optimal crop pattern and irrigation water resources allocation in the irrigated agriculture, in which the individual farmers and irrigation administrators put their views on three conflicting objectives: maximum of net returns, maximum of expected grain yield, and maximum of environmental returns. An interactive fuzzy multi-objective optimization (IFMOO) approach is applied to develop the sustainable crop planning for solving problems of vagueness and imprecision information related to data, model formulation and decision maker’s preferences involving in multi-objective linear programming (MOLP). The methodology is illustrated in a case study of crop pattern alternatives in Xingkaihu Lake Irrigation District of northeastern China. The incorporation of these socio-economic and environmental objectives demonstrates the capability of IFMOO approach and also works suitably in water resources management by trade-off procedures.